Police Authority Abuse Against Freedom of Expression: Case of Band Sukatani’s Intimidation - Rizky Wardana,; Iqbal Arysepta Imam Mahbi,; Nabila Annisa Fuzain, (Journal of Law Justice (JLJ), 2025)
This study aims to examine the abuse of authority by police officers against Band Sukatani's freedom of expression and analyze efforts to strengthen police institutions in preventing the recurrence of similar abuses of authority. The research method used is normative legal research with a legislative approach, a case approach, and an analytical approach to assess the conformity of the officers' actions with the applicable positive law provisions. The novelty of this research lies in its analytical focus on the case of intimidation of musicians as a form of restriction of freedom of expression carried out through institutional power mechanisms, thus providing a new perspective on systemic threats to the constitutional rights of citizens through the practices of law enforcement officials. The results of the study show that the actions of the police against the Sukatani Band were not based on criminal procedural law and did not reflect compliance with the principle of due process of law. This abuse of authority confirms the weaknesses in the internal and external oversight systems of the police and demonstrates the need for reform of the accountability mechanisms within the police institution. In addition, the study found that strengthening police institutions can be done by increasing the effectiveness of oversight functions by internal institutions such as Propam and external institutions such as Kompolnas, accompanied by the strict application of ethical and criminal sanctions against violators. The study concludes that preventing the abuse of authority by police officers requires a combination of strong oversight, institutional transparency, and consistent enforcement of sanctions so that police professionalism can be realized and citizens' right to freedom of expression can be protected.